Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s40463-022-00566-w
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of artificial intelligence implementation in the diagnosis of obstructive sleep apnea

Abstract: Background Obstructive sleep apnea is a common clinical condition and has a significant impact on the health of patients if untreated. The current diagnostic gold standard for obstructive sleep apnea is polysomnography, which is labor intensive, requires specialists to utilize, expensive, and has accessibility challenges. There are also challenges with awareness and identification of obstructive sleep apnea in the primary care setting. Artificial intelligence systems offer the opportunity for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In the same way, Brennan et al,. (30) concluded that while AI offers high accuracy in healthcare, human relationships and intuition cannot be replaced. Our ndings align with the doctor-in-the-loop AI framework that combines AI algorithms and medical expertise to enable more accurate and personalized diagnoses and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Brennan et al,. (30) concluded that while AI offers high accuracy in healthcare, human relationships and intuition cannot be replaced. Our ndings align with the doctor-in-the-loop AI framework that combines AI algorithms and medical expertise to enable more accurate and personalized diagnoses and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of machine learning and other automatic scoring algorithms offers a potential solution by automating the process of manual scoring, which the AASM sees great potential in Goldstein et al ( 2020 ). However, the development and application of machine learning are often prohibitively technical, requiring diverse knowledge of computer science to achieve (Giray, 2021 ; Brennan and Kirby, 2022 ). There is also a dire need for socio-technical alignment, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a dire need for socio-technical alignment, i.e. the multi-disciplinary collaboration between the computer scientists integrating the algorithms, and the professionals working in the context in which the algorithms are being integrated (Brennan and Kirby, 2022 ). The integration of AI, machine learning, or advanced data-driven decision-making of any kind into the workflow may move the industry professionals from a generative role (creating the outputs themselves) to the role of auditors, where they correct the output of the algorithms, and consult with computer scientists to tweak and alter the models to handle edge cases or incorrect generations by the algorithm (Grønsund and Aanestad, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few of the first studies exploring AI application in the diagnosis of OSA are focused on a generalized relapse neural network. This neural network shows a capability towards a precise rule in OSA from clinical statistics, with a precision and awareness (3).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show advanced systems where pulse oximetry's physiological data are included as well as electrocardiogram features. These systems are turning out to be a beneficial screening tool with a high negative predictive value (3).…”
Section: Introductionmentioning
confidence: 99%